Perlingungan Hukum Terhadap Anak Yang Menjadi Korban Kekerasan Seksual - Dian Putri Patrecia Lubis; Nur Fajarriah Indah; Oksep Adhayanto (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The rise in cases of violence and abuse against children in Indonesia is the background for this research. Basically, children are unable to protect their basic rights, so legal protection is needed provided by the state. The aim of this research is to determine the role of the government in providing protection for children who are victims of sexual violence, and to find out whether rehabilitation and psychological support is needed for children who are victims of violence. sexual. The method used is a normative legal method through a statutory approach and a case approach. The aim is to focus more on supporting materials specifically discussing sexual violence against children and protection for children as victims of sexual violence and harassment. As a result, the government and society have established institutions as shelter for children who are victims of sexual violence and harassment. Apart from that, this institution also provides rehabilitation and psychological support services to support the mental recovery of children who are victims of violence and sexual abuse. This case will have an impact on the child's psychological condition which can cause trauma and serious mental problems. This will have an impact on the child's future, disrupting the development process and hampering the child's potential to become a quality individual. With strong and firm legal protection, it is hoped that it can prevent and reduce cases of violence and sexual abuse against children in Indonesia.